Investigar em educação artística e ensino das artes visuais : balanço da produção e perspectivas actuais na Universidade de Lisboa (2007 - 2014) - Cabeleira, Helena dos Reis, 1978- (2018)
This article aims to map and to discuss the main theoretical-methodological lines of research that have been marking, from 2007 to 2014, the academic production in the field of artistic education (EA) and Visual Arts Education (EAV). Based on a research carried out from the UL’s Repository, this article sought to establish a ‘corpus documental’ composed of dissertations and reports whose analysis (both qualitative and quantitative) proposes to contribute to the knowledge and problematization of the current state of the art in the field